CACHE Challenge #2: Targeting the RNA Site of the SARS-CoV-2 Helicase Nsp13 - Herasymenko, Oleksandra; Silva, Madhushika; Abu-Saleh, Abd Al-Aziz A.; Ahmad, Ayaz; Alvarado-Huayhuaz, Jesus; Arce, Oscar E. A.; Armstrong, Roly J.; Arrowsmith, Cheryl; Bachta, Kelly E.; Beck, Hartmut; Berta, Denes; Bieniek, Mateusz K.; et al. (American Chemical Society, 2025)
A critical assessment of computational hit-finding experiments (CACHE) challenge was conducted to predict ligands for the SARS-CoV-2 Nsp13 helicase RNA binding site, a highly conserved COVID-19 target. Twenty-three participating teams comprised of computational chemists and data scientists used protein structure and data from fragment-screening paired with advanced computational and machine learning methods to each predict up to 100 inhibitory ligands. Across all teams, 1957 compounds were predicted and were subsequently procured from commercial catalogs for biophysical assays. Of these compounds, 0.7% were confirmed to bind to Nsp13 in a surface plasmon resonance assay. The six best-performing computational workflows used fragment growing, active learning, or conventional virtual screening with and without complementary deep-learning scoring functions. Follow-up functional assays resulted in identification of two compound scaffolds that bound Nsp13 with a K d below 10 mu M and inhibited in vitro helicase activity. Overall, CACHE #2 participants were successful in identifying hit compound scaffolds targeting Nsp13, a central component of the coronavirus replication-transcription complex. Computational design strategies recurrently successful across the first two CACHE challenges include linking or growing docked or crystallized fragments and docking small and diverse libraries to train ultrafast machine-learning models. The CACHE #2 competition reveals how crowd-sourcing ligand prediction efforts using a distinct array of approaches followed with critical biophysical assays can result in novel lead compounds to advance drug discovery efforts.